Unusual manifestations of a common gastrointestinal disorder. (13th May 2013) - Rajah, Karthik; Oliver, Mark R; McLeod, Liz; Orchard, David; Leal, Marcelo
Abstract We present an instructive case of a 13‐year old male who presented with bilateral scrotal redness, swelling and tenderness, but with a normal testicular exam. His scrotal swelling persisted despite treatment with intravenous antibiotics, and on further history he reported 2 years of intermittent upper lip swelling. After a referral to a dermatologist, a lip biopsy showed granulomatous changes and he was referred to the gastroenterology department. A gastroscopy and colonoscopy was performed and histology confirmed non‐caseating granulomas consistent with Crohn's disease (CD). Eighteen months after the diagnosis of CD he developed perianal disease with a fistula and distal anal stricture. He was successfully treated with insertion of a seton and escalation of therapy to azathioprine and infliximab. CD is a phenotypically diverse chronic inflammatory condition with an increasing incidence in Australia and other Western countries. Non‐typical presentations, such as perianal manifestations or orofacial granulomatosis, can be the only presenting symptom in CD, and this highlights the importance for a high degree of clinical suspicion. Genital involvement is rare, but reported.